Key in Brain: An Interesting Case of Civilian Penetrating Head Injury - Kotecha, Nitin; Diyora, Batuk; Patil, Swapnil; Giri, Sachin; Raka, Alka; Sharma, Alok (Indian Journal of Neurotrauma, 2016)
Civilian penetrating head injuries are not common, and the occurrence of such injuries in the pediatric population is rare. Pediatric penetrating head injuries are low-velocity injuries, resulting from household objects. Presentation entirely depends on the area of the brain involved. There are several management dilemmas related to the nature, size, shape, and location of the object, but always warrants removal of the foreign body into the operation theater. The outcome depends on the presenting neurological status of the patient, which reflects underlying parenchymal injury. We are reporting an interesting case of civilian penetrating head injury in a 5-year-old female child with a key in the brain. Computed tomographic scan of the brain revealed a household key penetrated through the right temporal bone. The patient underwent a surgical procedure for the removal of the key. She recovered well without any neurological deficit.
Keywords: foreign body; key in brain; penetrating head injury